2017
DOI: 10.3892/ol.2017.6426
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive microRNA-452 inhibits migration and invasion of breast cancer cells by directly targeting RAB11A

Abstract: Abstract. Breast cancer is the most common type of malignant tumor in females, and metastasis is the most common cause of breast cancer-associated mortality. Previous studies have identified that abnormal expression of microRNAs is commonly observed in human cancer and may be crucial for cancer metastasis. In the present study, microRNA-452 (miR-452) was investigated for its ability to act as a tumor suppressor in breast cancer. miR-452 expression was quantified in breast cancer tissue samples and cell lines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Feng et al [ 58 ] reported that miR-224 down-regulates the expression of fizzled 5 to inhibit the proliferation and migration of breast cancer cells. MiR-452, as a tumor-inhibitor of breast cancer, targets the RAB11A gene directly [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al [ 58 ] reported that miR-224 down-regulates the expression of fizzled 5 to inhibit the proliferation and migration of breast cancer cells. MiR-452, as a tumor-inhibitor of breast cancer, targets the RAB11A gene directly [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…They affect the stability of their target mRNAs, resulting in changes in the amount of target mRNA, which is one of the mechanisms of post-transcriptional regulation. Until now, some studies about the role of miR-452 have been performed in malignant neoplasms such as pancreatic cancer [46], glioma [47], lung cancer [48,49], and breast cancer [50]. A number of studies have indicated that miRNAs play roles in the regulation of many biological processes (migration, metastasis, cell proliferation, apoptosis, chemosensitivity, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Both Rab11A and Rab11B show significant changes in expression in various human cancer types with a prevalence for Rab11A ( Table 2 ). Other studies further suggest that Rab11A has an oncogenic role in several cancers including colorectal [ 69 ], pancreatic [ 70 ], breast [ 71 , 72 ], and lung cancers [ 73 ]. Rab11A overexpression promotes cellular transformation by regulating E-cadherin turnover in colorectal cancer cells [ 69 ].…”
Section: Internalization and Recycling Of Pars And Implications Inmentioning
confidence: 99%
“…In pancreatic cancer, Rab11A expression correlates with tumor-node-metastasis stage and promotes cell proliferation, cell cycle progression and invasion through GSK3β/Wnt/β-catenin pathway [ 70 ]. In breast cancer cells, downregulation of Rab11A by tumor suppressor miRNA miR-320a and miR-452 inhibits breast cancer growth, motility and invasion [ 71 , 72 ]. In lung cancer, high Rab11A levels correlate with advanced stage and poor survival [ 73 ].…”
Section: Internalization and Recycling Of Pars And Implications Inmentioning
confidence: 99%